2018
DOI: 10.4049/immunohorizons.1700069
|View full text |Cite
|
Sign up to set email alerts
|

Requirement for CD40/CD40L Interactions for Development of Autoimmunity Differs Depending on Specific Checkpoint and Costimulatory Pathways

Abstract: CD40/CD40L interactions play a critical role in immunity and autoimmunity. In this study, we sought to understand the requirement for CD40 signaling in the programmed cell death-1 (PD-1) checkpoint and CD28 costimulatory pathways important for maintenance of peripheral tolerance. Blocking either pathway can result in loss of self-tolerance and development of autoimmunity. We found that primary Sjögren’s syndrome (pSS) and autoimmune thyroid diseases (ATDs) that develop spontaneously in CD28-deficient IFN-γ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 78 publications
2
6
0
Order By: Relevance
“…Furthermore, mTOR acts as an energy metabolism pathway connecting the PD-1/PD-L1 immune checkpoint with T cells. PD-1/PD-L1 plays a crucial role in the occurrence and development of immune tolerance [32][33][34]. In the present study, the results showed that the expression of PD-1 and PD-L1 in the spleen and placenta was decreased in mTgpositive mice.…”
Section: Discussionsupporting
confidence: 54%
“…Furthermore, mTOR acts as an energy metabolism pathway connecting the PD-1/PD-L1 immune checkpoint with T cells. PD-1/PD-L1 plays a crucial role in the occurrence and development of immune tolerance [32][33][34]. In the present study, the results showed that the expression of PD-1 and PD-L1 in the spleen and placenta was decreased in mTgpositive mice.…”
Section: Discussionsupporting
confidence: 54%
“…The inhibition of CD40-CD40L pathway improves disease pathology in mouse models of lupus by reducing B cell activation, T follicular helper cell (T FH ) cell expansion, and the development of glomerulonephritis [12,13]. The inhibition of CD40-CD40L pathway also inhibits autoimmune pathology in models of SjS, autoimmune thyroid disease, and experimental autoimmune uveoretinitis [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…This cytokine has a crucial role not only in the development of T FH cells but also in the differentiation of B cells and the generation of humoral immune responses as well ( 66 ). Of note, in vitro analyses on T FH mediated B cell responses with blocking CD40L–CD40 interaction and neutralizing IL-21 effects in pSS were previously performed only in animal models ( 67 , 68 ). To further clarify the role of costimulation in our in vitro assay, anti-human CD40/TNFRSF5 and anti-human IL-21 antibodies were added together or by itself to inhibit T FH -B-cell interaction.…”
Section: Discussionmentioning
confidence: 99%